Phomotide A, a novel polyketide, from the endophytic fungus Phomopsis sp. CFS42. Issue 6 (6th February 2020) - Ma, Kai-Liang; Wei, Wen-Jun; Li, Hang-Ying; Wang, Liu-Di; Dong, Shi-Hui; Gao, Kun
Graphical abstract: Highlights: Isolation of two polyketides from Phomopsis sp. CFS42. Compound 1 possessed an unprecedented "C12 -C6 " carbon skeleton. Compound 1 was formed by Aldol reaction between two different polyketides. Abstract: Phomotide A (1 ), a polyketide featuring an unprecedented carbon skeleton with a rare C6 unit connected to a C12 unit via a CC bond, was obtained from the endophytic fungus Phomopsis sp. CFS42 which was isolated from the medicinally significant plant, Cephalotaxus fortunei Hook. Its structure was elucidated by spectroscopic data analyses and single crystal X-ray diffraction, as well as via electronic circular dichroism calculation. A plausible biogenetic pathway for 1 was also proposed.